An electrophysiologist’s guide to dorsal horn excitability and pain - Rivera-Arconada, Iván; Baccei, Mark L.; López-García, José A.; Bardoni, Rita (Frontiers in Cellular Neuroscience, 2025)
The dorsal horn of the spinal cord represents the first site in the central nervous system (CNS) where nociceptive signals are integrated. As a result, there has been a rapid growth in the number of studies investigating the ionic mechanisms regulating the excitability of dorsal horn neurons under normal and pathological conditions. We believe that it is time to look back and to critically examine what picture emerges from this wealth of studies. What are the actual types of neurons described in the literature based on electrophysiological criteria? Are these electrophysiologically-defined subpopulations strongly linked to specific morphological, functional, or molecular traits? Are these electrophysiological properties stable, or can they change during development or in response to peripheral injury? Here we provide an in-depth overview of both early and recent publications that explore the factors influencing dorsal horn neuronal excitability (including intrinsic membrane properties and synaptic transmission), how these factors vary across distinct subtypes of dorsal horn neurons, and how such factors are altered by peripheral nerve or tissue damage. The meta-research presented below leads to the conclusion that the dorsal horn is comprised of highly heterogeneous subpopulations in which the observed electrophysiological properties of a given neuron often fail to easily predict other properties such as biochemical phenotype or morphology. This highlights the need for future studies which can more fully interrogate the properties of dorsal horn neurons in a multi-modal manner.